The impact of the internet banking services on the satisfaction of the customer: a case study of the Agricultural Development Bank (ADB), Brong Ahafo Region, Ghana. - A Thesis Submitted In Partial Fulfilment Of The Award Of The Degree Of Master Of Business Administration (Strategic Management And Consulting). (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirements For The Degree Of Masters In Business Administration (Strategic Management And Business Consulting).